The Effectiveness of Transcultural Nursing Model to Improve Malaria Childcare - Payasan, Lalu Guntur; Situmeang, Lamria; Sulistiyani, Sulistiyani; Mebri, Elizabeth (Jurnal Keperawatan, 2024)
Malaria is endemic to Papua due to various factors, rendering its eradication a continual challenge. Nurses, as healthcare practitioners engaged in malaria management, frequently encounter clinical and sociocultural challenges. Consequently, transcultural nursing has emerged as an effective approach to improve pediatric malaria treatment. This study seeks to assess the efficacy of the transcultural nursing model in enhancing malaria care for children provided by their families. This quasi-experimental design used two groups: a control group and an intervention group, each comprising 50 participants. Data analysis utilized t-tests and a general linear model to evaluate the efficacy of the transcultural nursing model among groups subjected to three interventions over time The findings indicated notable disparities in child malaria care practices between the control and intervention groups, as demonstrated by both the t-test and general linear model analyses. This research concludes the transcultural nursing model can effectively address cultural barriers in the provision of nursing care for malaria.